(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The contemporary educational landscape increasingly emphasizes the integration of visual-cognitive competencies as a cornerstone for enhancing students’ analytical, interpretive, and problem-solving capabilities. This study explores the multifaceted nature of visual-cognitive skills, conceptualizing them as dynamic interactions between perceptual acuity, spatial reasoning, and knowledge representation. The research investigates methodological frameworks for assessing these competencies within educational contexts, drawing upon interdisciplinary perspectives from cognitive psychology, instructional design, and educational neuroscience.